Long-Term (>8 Years) Evaluation of Progression in Patients with Low-Pressure Glaucoma. Issue 6 (December 2015) - Erdem, Elif; Williams, Alice; Kuchar, Sarah Driscoll; Waisbourd, Michael; Spaeth, George L.
Purpose: To describe the long-term clinical course of patients with low-pressure glaucoma (LPG) and to assess the risk factors for disease progression. Methods: The Wills Eye Glaucoma Research Center retrospectively reviewed the charts of LPG patients with documented follow-up of >8 years between 2000 and 2013. Medical records were evaluated for systemic diseases, family history of glaucoma, best-corrected visual acuity, refractive error, treatments, central corneal thickness (CCT), intraocular pressure (IOP), IOP change after pupil dilation, optic disc evaluation, visual field (VF) mean deviation (MD), VF grading, and time to progression. Progression was determined when both disc and VF appeared to have worsened. Results: From 850 charts classified as LPG between 2000 and 2013, 49 eyes of 49 patients were included in our analysis. The mean (± SD) follow-up time was 9.3 (± 1.9) years. Glaucoma progressed in 25 eyes and remained stable in 24 eyes over the follow-up period. Eyes with progression had higher peak IOP (p = 0.043). There was a trend towards progression in patients with thinner CCT (p = 0.085) and disc hemorrhage (p = 0.098). Estimated annual change in MD was −0.57 dB in the progressing group and −0.10 dB in the stable group (p<0.0001). Conclusions: Nearly half of the patients with LPG showed glaucoma progression despite treatment after >8 years. High peak IOP was a significant risk factor for progression. Identifying patients at risk may warrant closer follow-up and more aggressive treatment in order to preserve visual function in patients with LPG.